Enculturating the Science of International Development: Beyond the WEIRD Independent Paradigm. (February 2023) - Thomas, Catherine Cole; Markus, Hazel Rose
Initiatives in international development and behavioral science rely predominantly on the independent models of the self and agency that are prevalent in individualist Western, Educated, Industrialized, Rich, and Democratic (WEIRD) cultural contexts. Programs that are guided by these independent models, explicitly or implicitly, as the default way of being and that neglect interdependent models can reduce the potential of development initiatives to advance poverty reduction and well-being in two ways. First, programs based solely on independent models of agency—centered on personal goals and values; self-advancement and self-expression; and autonomy—can limit the scope and effectiveness of the development science toolkit. Second, programs that are not responsive to interdependent ways of being—centered on relational goals and values; responsiveness to social norms, roles, and obligations; and social coordination—that are common in many Global South sociocultural contexts can be met with resistance or backlash. We propose that taking account of interdependent psychosocial tendencies is a promising way to diversify the behavioral science toolkit and to build a more comprehensive science of human behavior. Furthermore, culturally responsive program designs have the potential both to promote decolonized, inclusive approaches that preserve rather than override local ways of being and to enable diverse trajectories of societal development to flourish. We integrate experimental and descriptive research from psychology, economics, education, and global health to suggest how models of interdependent agency can be productively integrated into development program designs to advance quality of life in locally resonant ways.